Large Saharan dust storms: Implications for chlorophyll dynamics in the Mediterranean Sea. Issue 11 (25th November 2016) - Gallisai, Rachele; Volpe, Gianluca; Peters, Francesc
Abstract: We investigate the large (LDE) and very large (VLDE) Saharan dust deposition events that occurred between 2000 and 2007 and their short‐term impact on the dynamics of marine phytoplankton in the Mediterranean Sea. A total of 153 LDE were identified unevenly distributed over the years. Events were more frequent during winter, in the eastern Mediterranean, and autumn, when they affected both the western and the central Mediterranean. Most of the 31 VLDE occurred during winter and autumn in the central Mediterranean. The dynamics of chlorophyll after VLDE were studied as a proxy for phytoplankton response to atmospheric dust. A significant response of chlorophyll to dust addition was evident; this appeared to be especially true for the western Mediterranean where a chlorophyll increase of up to 345% was recorded, whereas in the central Mediterranean it was up to 146% and in the eastern Mediterranean up to 121%. Chlorophyll response behavior was quite heterogeneous probably as a result of the uniqueness of each VLDE, the differences between Mediterranean areas, the community structure of phytoplankton, and the interaction between bacteria and phytoplankton for new resources. An eastward decreasing trend in chlorophyll response was observed, which is in accordance with the relative importance of bacterial activity with respect to phytoplankton. The increase in mineral aerosols with increased aridity in the region together with the decrease in the depth of the mixed layer of the oceans should boost the importance of aerosols fueling marine production. Key Points: Large dust deposition events occur most frequently during winter (eastern) and autumn (western) Phytoplankton response to very large dust deposition events is significant with a decreasing eastward trend